THE TITLE HOW DO SRI LANKAN COMPANIES PERCEIVE CORPORATE SOCIAL RESPONSIBILITY? AN EMPIRICAL STUDY OF THE MOTIVATIONS UNDERLYING CSR PROJECTS AND REPORTING BY SRI LANKAN COMPANIES - Rajapakse, Bandara (My University, 2012)
This study investigates about the matters on which Sri Lankan companies base and carry out their Corporate Social Responsibilities and up to what extend those activities are based on good intensions. The study also looks into the fact as to what motivates the Sri Lankan companies to issue CSR reports. The study documents the motivations of modern corporations in issuing corporate social responsibility (CSR) reports to their stakeholders. It further demonstrates why these entities have suddenly become more moral or ethical. It identifies how Sri Lankan companies perceive Corporate Social Responsibility and their motivations of undertaking CSR projects and reporting to stakeholders of the same. An empirical methodology was used to gather and analyze the required information from 20 Sri Lankan companies listed in the Colombo Stock exchange. Study results suggest that Sri Lankan companies have different reasons for issuing CSR reports, for instance; in response to an increasing number of stakeholders requesting information on CSR, companies believe that doing so is good for business, to derive positive public relations benefits, to comply with the government’s request for them to issue information on CSR, etc. Information on corporate entities’ CSR activities is considered to be valuable by both academic researchers and business managers as it provides a working framework on which future studies can be based. In addition, it improves understanding of the social obligations which corporate entities owe to their stakeholders and society in general.